Critical review of the drivers and barriers for adopting net zero carbon procurement for construction projects - Robert Osei-Kyei; Timur Narbaev; Jin Xiaohua; Ursa Komac; Isaac Akomea-Frimpong; Gabriel Castelblanco (Sustainable Futures)
To meet the net zero 2050 target in construction, a net-zero carbon public procurement policy is needed. This paper adopts a systematic review approach to explore the drivers and barriers to adopting net-zero carbon procurement. The top three drivers include developing sustainable public procurement policies, increasing investment in low-carbon procurements, and high demand for green construction projects. The top three barriers include inadequate budget for net-zero procurement implementation, weak capacity in public and private institutions to implement net-zero policies, and low stakeholder involvement. The paper's findings provide insights for stakeholders to effectively adopt net-zero carbon procurement for construction projects.